PEMANFAATAN TEKNOLOGI SPEECH RECOGNITION UNTUK MELATIH KETERAMPILAN BERBICARA BAHASA ARAB SISWA MAN 2 PAYAKUMBUH - Rudiamon, Septika; Rahmadina, Rahmadina (Al-Fakkaar, 2025)
This study aims to describe the extent to which the use of speech recognition technology to train Arabic speaking skills of class X and class XI students of MAN 2 Payakumbuh. This study uses a quantitative approach with a descriptive type. The subjects of this study were all students of MAN 2 Payakumbuh who had difficulty speaking Arabic. The objects of this study were students of class X and class XI MAN 2 Payakumbuh who had trouble speaking Arabic. Data were collected through field observations, filling out questionnaires, collecting questionnaires via Google Forms, and other related documents. The data collected were processed using SPSS and the ANOVA test. The results of this study indicate that the use of speech recognition technology to train Arabic speaking skills has great potential in improving the communication of class X and class XI students of MAN 2 Payakumbuh. With this technology, students can train their Arabic speaking skills to be better because speech recognition technology can analyze specific weaknesses in speaking, and provide training that focuses on certain areas. Through instant application responses and regular practice, students' Arabic speaking skills can be improved to be more active and effective.